2019
DOI: 10.1111/abac.12166
|View full text |Cite
|
Sign up to set email alerts
|

The UK's Exit Charge from the EU: Insights from Modes of Accounting

Abstract: Whatever the final charge on the UK for leaving the EU, the money itself is relatively marginal to the former's public finances. However, this charge is politically sensitive and financially aggravating during one of the longest periods of fiscal austerity in the UK's history. The ways in which leaving is conceptualized have implications for any continuing financial obligations that must be managed within the context of fiscal austerity and political uncertainty. Yet, leaving the EU is a unique transaction: it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…According to derived data following preliminary results of the research was obtained after application of mean average formula (1) as it is shown in table 3. It was 0 values for the category "V" for 2017 [11][12][13], 2018 [14][15][16][17][18] and 2019 [19][20][21][22] publishing years, but in only one case in 2020 [23] all categories had their respective values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to derived data following preliminary results of the research was obtained after application of mean average formula (1) as it is shown in table 3. It was 0 values for the category "V" for 2017 [11][12][13], 2018 [14][15][16][17][18] and 2019 [19][20][21][22] publishing years, but in only one case in 2020 [23] all categories had their respective values.…”
Section: Resultsmentioning
confidence: 99%
“…In 7 cases out of 20 inspected materials there was no mentioning about any technology relating to financial services as seen in table 4. Those are from article 3 [27], 4 [28], 5 [11], 6 [12], 8 [14], 9 [15] and 13 [19]. While the issue of traditional banking institution and globalization was discussed or at least touched in all 20 articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been argued that austerity has: impacted on child poverty and massively increased the necessity for food banks (Mueller, ); caused major reductions in the affordable housing program (The Guardian, ); and resulted in significant reductions in local authority spending (and service provision) in areas such as refuse collection, road maintenance, and libraries (LGA, 2019). Moreover, within this Special Issue, and within a context of austerity, Heald and Wright () explore the calculation and impact of the UK's final Brexit bill for departing the EU. In particular, they examine the use of accounting (and other) numbers with respect to the UK's negotiating position relating to the possible charge.…”
Section: The Impact Of Austerity and Changed Political Realitiesmentioning
confidence: 99%